Different storage and freezing protocols for extracellular vesicles: a systematic review - Shahin Ahmadian; Negin Jafari; Amin Tamadon; Alireza Ghaffarzadeh; Reza Rahbarghazi; Mahdi Mahdipour (Stem Cell Research & Therapy)
Abstract Background Extracellular vesicles (EVs) have been considered promising tools in regenerative medicine. However, the nanoscale properties of EVs make them sensitive to environmental conditions. Optimal storage protocols are crucial for maintaining EV structural, molecular, and functional integrity. This systematic review aimed to gather evidence on the effects of various storage protocols on EV characteristics and integrity. Strategy A comprehensive search was conducted for original studies investigating the impacts of storage temperature, freezing techniques, freeze-thaw cycles, and stabilizing strategies on EV concentration, size distribution, morphology, cargo content, and bioactivity. Results from 50 included studies were analyzed. Results Data indicated that rapid freezing procedures and constant subzero temperatures (optimally − 80 °C) resulted in appropriate EV quantity and cargo preservation. Subjecting EVs to multiple freeze-thaw cycles decreased particle concentrations, RNA content, impaired bioactivity, and increased EV size and aggregation. Electron microscopy revealed vesicle enlargement, and fusion, along with membrane deformation after being exposed to substandard storage protocols. The addition of stabilizers like trehalose helped EVs to maintain integrity. Of note, storage in native biofluids offered improved stability over purified EVs in buffers. Conclusion Data emphasize the critical need for precise storage protocols for EVs to ensure reproducible research outcomes and clinical applications. Further studies using reliable methods are necessary to create specific guidelines for improving the stability of EVs in various applications.